HAMBATAN-HAMBATAN KOMUNIKASI KEPEMIMPINAN REGIONAL DI PEMERINTAHAN - Evawani Elysa Lubis (Universitas Riau, 2012)
Obstacles Communication Regional Leadership in Government. This study aims to findout and considers the communication barriers regional leadership (head area) is motivated by the conflict inKampar Regency Administration. Then also to find out how the implementation of organizationalcommunication could develop into a conflict within a formal structure to the local government level. Themethod used in this study is to gather descriptive qualitative data from informants. The data collected wasprocessed qualitatively, by stating in the narrative information from each informant about the issues understudy. The results showed that the implementation of organizational communication is not running smoothlybecause of communication barriers. Leadership style is authoritarian tendencies, communication styles, aswell as poor communication competency is most triggers of conflict.